PERHITUNGAN TEKANAN DARI ALIRAN RADIAL FLUIDA INKOMPRESSIBLE PADA RESERVOIR - Satiawati, Listiana; Harin Widiyatni; Dalimunthe, Yusraida Khairani (Petro : Jurnal Ilmiah Teknik Perminyakan, 2023)
This research is a continuation of several previous studies that have been published, in general studying fluid flow in reservoirs. There are 2 fluid flows in reservoirs, namely linear and radial, while there are 3 types of fluids, namely incompressible, slightly compressible and compressible. In this study, the pressure and pressure drop of incompressible fluids at a certain distance from the well to the reservoir are calculated. The equation used to calculate fluid pressure is derived from the Darcy Equation. To obtain accurate data, the calculations are carried out repeatedly with 1 ft intervals, namely to get an overview of changes in pressure. The initial calculations were done manually but because the calculations were quite difficult and repetitive, the Fortran software was used to calculate them. Numerical calculations were carried out with some rock permeability data. The calculated results obtained pressure characteristics from a certain radius to the well with several values of rock permeability and these results are expressed by a graph between pressure and radius.